Sistem Keamanan Perumahan Pendekteksi Plat Nomor Kendaraan Menggunakan Kamera ETLE Korlantas - Hanief Aditiawan; Mila Amelia; Safru Rozaky; Sofyan Mufti Prasetiyo (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The high crime rate in big cities makes some people worry about theft, especially theft in residential areas. Homeowners are sometimes anxious to leave the house empty, especially with the increase in theft, especially vehicles in residential areas. This study proposes to design a surveillance camera system to detect the entry and exit of vehicles in housing, so that security can easily monitor and monitor incoming and outgoing vehicles with mobile devices installed at the gate in and out of the housing. The design of a surveillance camera system utilizes ETLE Kapolnas camera technology which is equipped with ANRP feature which can detect blacklisted vehicles, fake license plates and not registered in the system, besides that this camera is also equipped with an auto capture feature for license plates that are not registered in identification registration. For license plates that cannot be identified by the system, the system will automatically give a warning which can later be checked by the security on duty. This is intended to control the entry and exit of people in housing as a warning in an effort to prevent acts of theft.